2019
DOI: 10.1111/cid.12812
|View full text |Cite
|
Sign up to set email alerts
|

Implant failures and age at the time of surgery: A retrospective study on implant treatment in 2915 partially edentulous jaws

Abstract: Purpose: To further report and analyze data on the prevalence of implant failures related to age at surgery in partially edentulous jaws.Materials and Methods: Altogether, 2915 partially edentulous jaws (Kennedy Class I and II) were consecutively treated with 9167 implants over a 30-year period (1986-2015) in one referral clinic. All implant failures were consecutively recorded and the first event of implant failure was analyzed in relation to patient age at implant surgery.Results: A total of 2453 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
5
19
0
1
Order By: Relevance
“…This pattern was observed in the present univariable analysis (Table ; total group) and is consistent with implant‐level results reported by others in mixed populations using comparable analytical approaches . However, when patients were analyzed strictly according to clinical conditions in multivariable analyses also including nonlinear statistical methods, another pattern was revealed . Partially edentulous patients (Kennedy Class I and II) were recently reported to present a higher risk of implant failures when aged 45‐55 years, with a lower risk observed in younger and older age groups .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This pattern was observed in the present univariable analysis (Table ; total group) and is consistent with implant‐level results reported by others in mixed populations using comparable analytical approaches . However, when patients were analyzed strictly according to clinical conditions in multivariable analyses also including nonlinear statistical methods, another pattern was revealed . Partially edentulous patients (Kennedy Class I and II) were recently reported to present a higher risk of implant failures when aged 45‐55 years, with a lower risk observed in younger and older age groups .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a significant association between the risk of implant failure and age at surgery is not observed in the present young single implant group, but a significantly higher risk is associated with an older age when young patients treated with a single implant are here pooled with older, high‐risk edentulous patients (Tables ). However, a significantly decreased risk of implant failures with increasing age was observed when only edentulous patients were included in the analysis (Tables 3‐5), in accordance with previous studies . This finding further exemplifies the importance of detailed presentations and considerations of patient distributions in a study, as suggested by STROBE…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations